Red Barber : the life and legacy of a broadcasting legend - Hiltner, Judith R.; Walker, James Robert (University of Nebraska Press, 2022)
"This biography of sports announcer Red Barber (1908-92) puts his life and broadcasting career in the context of twentieth-century American life and explores his own personal journey"--